The fiscal consequences of deflation: Evidence from the golden age of globalization - Afonso, António (2022)
We study the fiscal consequences of deflation on a panel of 17 economies in the first wave of globalization,between 1870 and 1914. By means of impulse response analyses and panel regressions, we find that a 1%fall in the price level is associated with an increase in the public debt ratio of about 0.23–0.33 percentagepoints and accounting for trade openness, monetary policy and the exchange rate raises the absolute valueof the coefficient on deflation. For government revenue, lagged deflation comes out with a statisticallysignificant negative coefficient, while government primary expenditure seems relatively invariant tochanges in prices. Moreover, a 1% decrease in the price level is associated with a rise in the revenue toGDP ratio of about 0.02 percentage points, a reverse Olivera-Tanzi effect.